Qing-Re-Xiao-Zheng-Yi-Qi formula relieves kidney damage and activates mitophagy in diabetic kidney disease - Wu, Qiaoru; Yan, Runze; Yang, Hanwen; Wang, Yixuan; Zhang, Chao; Zhang, Jiale; Cui, Zhaoli; Wang, Yaoxian; Sun, Weiwei (Frontiers in Pharmacology, 2022)
Introduction: Qing-Re-Xiao-Zheng-Yi-Qi Formula is an effective prescription in diabetic kidney disease treatment, we have confirmed the efficacy of Qing-Re-Xiao-Zheng therapy in diabetic kidney disease through clinical trials. In this study, we investigated the mechanisms of Qing-Re-Xiao-Zheng-Yi-Qi Formula in the treatment of diabetic kidney disease. Methods: We used Vanquish UHPLCTM to analyze the chemical profiling of Qing-Re-Xiao-Zheng-Yi-Qi Formula freeze-dried powder. We constructed diabetic kidney disease rat models induced by unilateral nephrectomy and high-dose streptozocin injection. We examined blood urea nitrogen, serum creatinine, serum glucose, total cholesterol, triglyceride, serum total protein, albumin, alanine aminotransferase, aspartate aminotransferase and 24 h urinary total protein in diabetic kidney disease rats. The renal pathological changes were observed by HE, Masson, PAS stanning and transmission electron microscopy. The levels of fibrosis-related proteins and mitophagy-related proteins were detected by western blot analysis. We also conducted an immunofluorescence co-localization analysis on podocytes to further investigate the effect of Qing-Re-Xiao-Zheng-Yi-Qi Formula treatment on mitophagy. Results: A total of 27 constituents in Qing-Re-Xiao-Zheng-Yi-Qi Formula were tentatively identified. We found PINK1/Parkin-mediated mitophagy was inhibited in diabetic kidney disease. Qing-Re-Xiao-Zheng-Yi-Qi Formula treatment could raise body weight and reduce renal index, reduce proteinuria, improve glycolipid metabolic disorders, ameliorate renal fibrosis, and reduce the expression of Col Ⅳ and TGF-β1 in diabetic kidney disease rats. Qing-Re-Xiao-Zheng-Yi-Qi Formula treatment could also increase the expression of nephrin, activate mitophagy and protect podocytes in diabetic kidney disease rats and high glucose cultured podocytes. Conclusion: PINK1/Parkin-mediated mitophagy was inhibited in diabetic kidney disease, and Qing-Re-Xiao-Zheng-Yi-Qi Formula treatment could not only ameliorate pathological damage, but also promote mitophagy to protect podocytes in diabetic kidney disease.